Apologies and damages: the moral demands of tort law as a reparative mechanism - Pino-Emhart, A (2015)
This thesis seeks to justify on moral grounds the existence of tort systems. The argument is that corrective justice is necessary but not sufficient to succeed at this task. Corrective justice is necessary because it is the only principle that can adequately justify the bilateral structure of tort litigation between claimants and defendants, and full compensatory damages as the default remedy in most tort systems. However, it is argued that the critiques to corrective justice lead us to the important lesson that tort law is more than just corrective justice. Three gaps of corrective justice are identified: the equivalence between gains and losses, the definition of what counts as a tort, and the diversity of remedies. The thesis offers a solution to these problems based on the values of restorative and distributive justice. It is argued that restorative justice plays an important role in tort law, providing an apologetic framework for material compensation (the message that money awards communicate), but especially for symbolic remedies, such as apologies, nominal damages, non-pecuniary damages, punitive damages, and gain-based damages, solving the diversity of remedies problem. This restorative framework of tort remedies is compatible with corrective justice. Distributive justice also plays an important role in tort law. Even though corrective and distributive justice are conceptually separate concepts, in the context of tort law they cannot be separated. It is argued that the definition of what counts as a tort involves a distributive task. Following this argument, the thesis argues that there is a distributive uneasiness in tort law, because tort law protects some interests regardless of how they were acquired, and regardless of whether their distribution amounts to an unfair distribution of resources. It is suggested that the distributive mechanism of insurance can solve, or at least ameliorate, this uneasiness.